ANALYSIS OF AVAILABILITY AND NEED FOR HEALTH FACILITIES BASED ON POPULATION GROWTH IN SEI RAMPAH URBAN - Feby Milanie; Bety Zannatun; Jericho Alpasyakh Hutabarat; Muhammad Arief Kurniawan; Ramayani Marpaung (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to analyze the availability and future needs of health facilities based on population growth in the Sei Rampah urban area, Serdang Bedagai Regency. The continuous increase in population demands adequate health infrastructure to ensure equal access to healthcare services for all residents. The research employs the compound interest projection method using secondary time-series data from 2020 to 2025 obtained from the Central Bureau of Statistics (BPS) of Sei Rampah District. The results show that the population of Sei Rampah Urban Area is projected to reach 60,799 people by 2045. Based on the Indonesian National Standard (SNI) 03-6981-2004, the required number of health facilities by 2045 is estimated at 93 units with a total land area of ​​approximately 3,864 hectares. The projected needs consist of 49 integrated health service posts (Posyandu), 24 community health centers, 2 maternity clinics, 1 primary health center (Puskesmas), 12 private medical practices, 2 pharmacies, and 2 auxiliary health centers (Pustu). The findings of this study are expected to serve as a reference for local governments in planning the provision of health facilities proportionally and sustainably in line with future population growth.